2009
DOI: 10.1021/je900777q
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressures and Enthalpies of Combustion of the Dihydroxybenzoic Acid Isomers

Abstract: The Knudsen mass-loss effusion technique was used to measure the vapor pressures at different temperatures of the following dihydroxybenzoic acids : 2,3-dihydroxybenzoic acid, between (345.22 and 363.18) K; 2,4dihydroxybenzoic acid, between (376.22 and 392.11) K; 2,5-dihydroxybenzoic acid, between (372.14 and 388.92) K; 2,6-dihydroxybenzoic acid, between (347.14 and 365.17) K; 3,4-dihydroxybenzoic acid, between (387.12 and 403.26) K; and 3,5-dihydroxybenzoic acid, between (345.22 and 363.18) K. From the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
4
9
1
Order By: Relevance
“…Regarding the enthalpy of fusion, the literature values are much more uncertain and less consistent with each other. The results found in this work for protocatechuic and α-resorcylic acids are very close to those measured by Vecchio [56] and Monte et al [59], respectively. In the case of gentisic acid, only one value was found in the literature for the enthalpy of fusion, which is quite smaller than the value obtained in this work.…”
Section: Fusion Propertiessupporting
confidence: 92%
“…Regarding the enthalpy of fusion, the literature values are much more uncertain and less consistent with each other. The results found in this work for protocatechuic and α-resorcylic acids are very close to those measured by Vecchio [56] and Monte et al [59], respectively. In the case of gentisic acid, only one value was found in the literature for the enthalpy of fusion, which is quite smaller than the value obtained in this work.…”
Section: Fusion Propertiessupporting
confidence: 92%
“…In a previous paper [6], we have reported the study of two 2-carbon-bonded substituted phenols (substituent = CHO and CONH 2 ). In order to complement the experimental thermochemical data on compounds with a substructure containing a phenol group linked to carbon-bonded substituents containing the C@O group, we extend our research to the study of other hydroxybenzaldehyde derivatives, namely the 3-and 4-hydroxybenzaldehyde isomers and the 3,5-di-tert-butyl-2-hydroxybenzaldehyde [7], reported here, and to the dihydroxybenzoic acid isomers [7,8]. Very recently, there was reported both a theoretical and experimental thermochemical study for the 2-and 4-hydroxybenzaldehydes [9], these being experimental results along with the previously reported values for 2-hydroxybenzaldehyde [6] and the comments by Gomes [10], who did also a complementary theoretical study.…”
Section: Introductionmentioning
confidence: 99%
“…The enthalpy of sublimation (DH sub ) of all the x,ydihydroxybenzoic acid isomers were investigated to determine if this influenced their performance, but it was found that their sublimation enthalpies were not sufficiently different to rationalize their performance as UV MALDI matrices. Our data for these compounds are given in Table 3 where the original data has been corrected to 298.15 K using the method of Chickos et al [77] Later work by Monte et al published the vapour pressures of the same materials as determined by Knudsen effusion [78]. When the enthalpy of vaporisation is calculated using the ClausiusClapeyron relation and reduced to 298.15 K by the same method then reasonable agreement between both techniques can be obtained.…”
Section: Temperature-jump and Modulated Heating Profilesmentioning
confidence: 84%
“…The temperature program consisted of temperature jumps of 2 K with an isothermal segment of 20 min between each step and full experimental details can be found elsewhere [73]. By extrapolating the rate of mass change data to the point at which the temperature Table 2 Enthalpies of sublimation of x,y-dihydroxybenzoic acids from temperature-jump thermogravimetry [79] and Knudsen effusion [78]. Fig.…”
Section: Temperature-jump and Modulated Heating Profilesmentioning
confidence: 99%